SHM_415742_HST_3D Thick-Butted Stone Axe with a Flared Edge - Qallaki, Ylber; Lernestål, Erik; Strandberg, Caroline; National Historical Museums (National Historical Museums, 2026)
Photogrammetric 3D model of a Late Neolithic thick-butted stone axe with a flared edge collected in Sweden and currently held in the collections of the National Historical Museums in Stockholm.

Link to the Dynamic Collection platform

https://dyncoll.ht.lu.se/artifact_view.php?item=696

Link to Sök I Samlingarna

https://samlingar.shm.se/object/FAE2971A-DDC1-4421-B1D7-E4720E841C53
Keywords: 3D Model; Museum Object; Archaeology; Archaeology; Photogrammetry; Archaeology/history; History and archaeology; Dynamic Collections; Swedish Late Neolithic; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi